Urban Growth and Housing Supply across Australian Regional Areas - Norton, James Robinson (2012)
Developments in the study of economic geography have highlighted the importance of considering economic phenomena across space. As a sparsely populated, yet highly urbanised country, the modelling of Australia’s regional economy should be of interest to researchers, policy makers and business practitioners alike. This dissertation explores the relationship between regional urban grown and region specific elasticity of supply for housing. An interregional equilibrium model of urban growth with housing supply is outlined from the literature. The empirical work includes the direct estimation of supply elasticity measures for housing across 43 regional urban centres in Australia. Further results are provided to query the predictions of the model - that housing supply elasticity will have particular implications for urban growth dynamics - which yield interesting insights for further research. In conclusion, policy implications concerning both regional growth dynamics and housing affordability are discussed.